Faktor-Faktor Yang Berhubungan Dengan Perilaku Penerapan Hand Hygiene Di RSUD LANTO Dg PASEWANG - Hamdana Hamdana; Nadia Alfira; Irfanita Nurhidayah (Politeknik Kementerian Kesehatan Banjarmasin, 2021)
Hospital-acquired or nosocomial infections are a major threat to patients. Hand hygiene prevents cross-infection in hospitals, but implementation of Hand Hygiene according to recommended guidelines is often poor by healthcare workers. The research objective was for factors related to the application of hand hygiene at Lanto Dg Pasewang Regional Hospital. This type of choreational research design with cross sectional research approach. The study population was 180 people, the sample technique used purposive sampling and the sample in this study there were 36 respondents in Lanto Hospital with Pasewang. Data collection tools in the form of questionnaires and observation sheets. Based on the results of statistical tests using the Chi-square test, the value of knowledge was obtained: p = 0.631> α = 0.05, age: p = 0.729> α = 0.05, attitude: p = 0.715> α = 0.05, education: p = 1,000> α = 0.05, tenure: p = 0.376> α = 0.05. there is no relationship between knowledge, age, attitude, education and years of service on the behavior of the application of hand hygiene in RSUD Lanto and Pasewang. There is no relationship between knowledge, age, attitude, education and years of service on the behavior of the application of hand hygiene in RSUD Lanto and Pasewang. Nurses are advised to increase knowledge and implement hand hygiene through infection reduction training programs to reduce the incidence of hospital infections. Keywords: Behavior, Age, Knowledge, Education, Attitude, Tenure, Hand Hygiene